Integration of Maqāṣid Sharia and Social Philanthropy in the Economic Empowerment of the Shrimp Pond Labor Community - Mukhlishin Mukhlishin (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2025)
The pond industry plays a crucial role in shaping the social and economic landscape of local communities. However, the economic empowerment of pond workers has yet to demonstrate a substantial positive impact on broader community welfare. This study examines how economic empowerment initiatives targeting pond worker communities contribute to their well-being, using the Maqāṣid Sharia framework and evaluating the role of social philanthropy integrated by PT. Panen Berkat Sejahtera Bersama. Data were collected through unstructured interviews and direct observation at pond sites, focusing on the economic effects experienced by workers’ families. Findings indicate that the pond industry significantly enhances community economic welfare. It provides permanent employment with relatively stable income for workers, while seasonal harvests offer temporary work and bonuses that boost earnings for casual laborers. This improved income contributes to better living standards, including home renovations, children's education, and the fulfillment of daily necessities. From the perspective of Maqāṣid Sharia, the industry contributes positively to several key dimensions: ḥifẓ māl (protection of wealth), ḥifẓ ‘aql (protection of intellect), ḥifẓ dīn (protection of religion), and ḥifẓ nasl (protection of progeny). The study highlights the importance of supportive policies that strengthen the pond sector by expanding access to education, vocational training, and sustainable employment, thereby enhancing the overall welfare of pond workers.